Fe2Co2Nb2O9: a magnetoelectric honeycomb antiferromagnet. Issue 40 (27th September 2021) - Maignan, Antoine; Martin, Christine; Tailleur, Elodie; Damay, Françoise; Mostovoy, Maxim; Wang, Xiao; Hu, Zhiwei; Lin, Hong-Ji; Chen, Chien-Te; Tjeng, Liu Hao; Suard, Emmanuelle; Fauth, François
Abstract : In Fe2 Co2 Nb2 O9, magneto-electric ME poling induces below T N an electric polarization P whose magnitude increases with the magnetic field H . Large P values and steep P responses to H are explained by a microscopic model based on the random distribution of Fe and Co. Abstract : Fe4 Nb2 O9 and Co4 Nb2 O9 are antiferromagnetic compounds belonging to the M4 M′2 O9 series (M = Mn, Fe, Co; M′ = Nb, Ta), whose structure ( P 3̄ c 1) derives from the Cr2 O3 corundum one. By mixing cobalt and iron in a 1 : 1 ratio, an Fe2 Co2 Nb2 O9 oxide has been synthesized. Its structural, magnetic and electric characterization studies confirm that its unit cell volume ( V = 331.19(1) Å 3 ), Néel temperature ( T N = 58 K) and dielectric permittivity are intermediate between those of the Fe4 Nb2 O9 and Co4 Nb2 O9 end members. The neutron diffraction study evidences an Fe:Co random occupation of the (4d) Wyckoff sites. Its antiferromagnetic structure, refined in the C 2/ c ′ magnetic space group, shows magnetic moments in the planes of the honeycomb (HC) layers of the M4 M′2 O9 structure, and stacked along c, as for Fe4 Nb2 O9 and Co4 Nb2 O9 . However, the magnetic field induced magnetization M ( H ) of Fe2 Co2 Nb2 O9 below T N differs strongly from both end members, exhibiting a sublinear dependence. A similar rounded shape of the electric polarization P ( H ) curve is evidenced, in marked contrast to the linear M ( H ) and P ( H ) behaviours observed below the spin-flop magnetic field for this class of linear magnetoelectric materials. As a result, Fe2 Co2 Nb2 O9 exhibits larger P values and steeper P responses to H at low H than both Fe4 Nb2 O9 and Co4 Nb2 O9 end members. This result is explained by a microscopic model based on the Fe and Co mixed occupation. Substitutional disorder locally allows for stronger magnetoelectric couplings and its effect does not cancel on average. This chemical substitution effect opens a new route to enhance the magnetoelectric response of honeycomb antiferromagnets.